STUDY OF THE STRESS-STRAIN STATE OF A MONOLITHIC REINFORCED CONCRETE QUAY WALL - Naboka, A.; Petrenko, D. (Municipal economy of cities. Series: «Economy science», 2025)
The scientific work is devoted to a comprehensive study of the stress-strain state of the quay wall, an industrial facility that has been under construction for a long time. A practical assessment of the physical and mechanical characteristics of the materials used in the construction was carried out. Laboratory verification of the obtained data was carried out using the current methodology and in accordance with the requirements of Ukrainian building codes. When constructing piers, materials with various properties are used: wood, concrete, reinforced concrete, steel. Often, pier structures are made of different materials. For example, the base is made of wooden or metal piles, and the deck is made of reinforced concrete. However, the most common are reinforced concrete or concrete structures. Quay wall – is a monolithic reinforced concrete structure, the basis for the construction of the pier as a whole. During a detailed inspection of the retaining wall structures, a visual inspection of the building structures, as well as its individual elements, was carried out to determine their technical condition, degree of physical wear and tear, and bearing capacity. During the field study, the retaining wall was studied in detail. The geometric characteristics of the structures were established. The results of the study show the following: during the visual inspection of the structure, some defects were found, including; the erected sections of the quay wall (1, 2, 3, 7) have a color that is not typical of high-quality concrete. The presence of some cracks. Nevertheless, the opening width is permissible within 0.3 mm. The experimental algorithm for establishing the physical and mechanical characteristics of the quay wall deformability, which has been under construction for a long time, has been improved. A comprehensive study of building structures has been carried out; the actual characteristics of materials have been determined. An additional expert analysis of the structural system of the quay wall has been carried out. Based on the results of the comprehensive theoretical and experimental studies, proposals have been made for further safe operation. The results obtained can be used by engineers in the future to establish the causes of disruptions in the technological process of production.